Investigation on strain dependence of metadynamic recrystallization behaviors of GH4169 superalloy. (March 2018) - Chen, Xiao-Min; Lin, Y.C.; Li, Xin-He; Chen, Ming-Song; Yuan, Wu-Quan
Abstract: The metadynamic recrystallization (MDRX) behaviors of a solid-solution GH4169 superalloy were studied by two-pass hot compression tests. The effects of pre-strain (deformation degree of the first pass) on MDRX behaviors were analyzed. Results show that the MDRX behaviors intensely depend on the pre-strain. The MDRX fraction first increases and then drops with the increased pre-strain. This is because a relatively large pre-strain can facilitate the nucleation of dynamic recrystallization (DRX) grains, which promotes the subsequent MDRX behaviors. However, due to the decreased stored deformation energy at relatively high pre-strain, the number of DRX grains cannot continuously increases. Thus, the MDRX fraction is reduced with the further increase of pre-strain. The segmented MDRX kinetics models were proposed and validated to describe the significant strain dependence of MDRX behaviors. Highlights: Metadynamic recrystallization (MDRX) behaviors of a solid-solution GH4169 superalloy are studied. MDRX fraction first increases and then drops with the increased pre-strain. Large pre-strain can facilitate the nucleation of DRX grains, promoting the subsequent MDRX behaviors. Segmented MDRX kinetics models are proposed to describe strain dependence of MDRX behaviors.